Unearthing Biblical Wisdom for Active Learning: An Interactive Model of Christian Education in the Age of Digital Technology - Okta, Oktavianus Rangga; Yuliana, Dewi; Mailoor, Anastacia Jennifer Alexandrina (Sekolah Tinggi Teologi Transformasi Indonesia, 2024)
Amidst the rapid pace of technological development, the world of education has undergone major changes, including in the way Christianity is taught. Traditional teaching methods, which often focus on lectures and memorization, are now faced with new demands. Christian Religious Learning is not only intended to instill theological knowledge, but also to guide students in understanding and applying Bible teachings in their lives, both personally and socially. This study uses a qualitative method with a literature study approach to explore interactive learning models in Christian religious education in the digital era. Education in the Bible begins with the recognition that all true wisdom and knowledge comes from God. The wisdom of the Bible has strong relevance in dealing with contemporary issues, because the principles taught in the Bible are timeless. In a world that is constantly changing, biblical values such as justice, love, and forgiveness remain solid moral guidelines. Technology has provided wider access to Christian religious learning materials. Through the internet, Christians can access the Bible, daily devotions, sermons, and theological resources anytime and anywhere. This study shows that an interactive approach to Christian religious education significantly improves students' understanding and engagement with Bible teachings. Other findings confirm that integrating digital learning and biblical values not only improves cognitive learning outcomes but also deepens students’ spirituality. The findings of this study are based on the development of an innovative teaching paradigm that combines traditional Bible with digital technology innovations that have not previously been systematically applied in Christian education